Healing process of venous ulcers of difficult healing in treatment with an Unna's boot - Sousa, Érica do Nascimento (2022)
Objective: to analyze the healing process of venous ulcers treated with an Unna’s boot. Methods: longitudinal study, prospective, with 14 individuals with chronic venous ulcers, followed at four different moments of time. Data collection was based on clinical and sociodemographic profile and clinical evaluation of the lesions. Data were analyzed using the Friedman test. Wilcoxon’s signed ranks test was used to compare means, and for multiple comparisons Bonferroni’s correction was used (p<0.05). Results: the Bonferroni post hoc test revealed a reduction in pain scores (p=0.038), amount of exudate (p=0.005) and dry border (p=0.044). Improvement in healing was observed by means of the Pressure Ulcer Scale for Healing (p=0.004) after use of the Unna boot between the first and fourth moments. Conclusion: there was a reduction in the Pressure Ulcer Scale for Healing indicators, pain, amount of exudate and dry border of the lesion in patients using Unna’s boot after four weeks. Contributions to practice: the need to manage indicators such as Pressure Ulcer Scale for Healing classification, pain, amount of exudate, and dry border based on the Unna Boot is highlighted.